1985
DOI: 10.1111/j.1432-1033.1985.tb09203.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative inactivation of an extramitochondrial acetyl-CoA hydrolase by autoxidation of l-ascorbic acid

Abstract: The activity of acetyl-CoA hydrolase (dimeric form) purified from the supernatant fraction of rat liver was shown to have a half-life ( t 1 / 2 ) of 3 min at 0"C, but to be stable at 3 7 T (t1/2 = 34 h) Biochemistry 22, 584-5901, Incubation of the purified enzyme with L-ascorbic acid (AsA) at 3 7~' C resulted in inactivation of the enzyme ( t l j z = 90 min at 2 mM AsA). The extent of inactivation was greatly enhanced by addition of transition metal ions (Cu2+, Fez', and Fe3+). Thiol reducing agents, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Later its role was re‐characterised as mainly being active for the CoA transfer from succinyl‐CoA to acetate, implying an acetate detoxification, and only a minor acetyl‐CoA‐hydrolase activity . Furthermore, ROS induced oxidative inactivation of acetyl‐CoA hydrolase, purified from the supernatant fraction of rat liver, was reported by Nakanishi et al Orlandi et al provided evidence in yeast that ACH1 inactivation severely impairs mitochondrial functions, which influences the acetate metabolism, the chronological lifespan and the occurrence of apoptosis. Additionally, Eisenberg et al , showed that deletion of the ACH1 caused cytosolic accumulation of the acetyl‐CoA precursor acetate, which led to hyperactivation of nucleocytosolic acetyl‐CoA‐synthetase (Acs2p), responsible for conversion of acetate to acetyl‐CoA.…”
Section: Resultsmentioning
confidence: 96%
“…Later its role was re‐characterised as mainly being active for the CoA transfer from succinyl‐CoA to acetate, implying an acetate detoxification, and only a minor acetyl‐CoA‐hydrolase activity . Furthermore, ROS induced oxidative inactivation of acetyl‐CoA hydrolase, purified from the supernatant fraction of rat liver, was reported by Nakanishi et al Orlandi et al provided evidence in yeast that ACH1 inactivation severely impairs mitochondrial functions, which influences the acetate metabolism, the chronological lifespan and the occurrence of apoptosis. Additionally, Eisenberg et al , showed that deletion of the ACH1 caused cytosolic accumulation of the acetyl‐CoA precursor acetate, which led to hyperactivation of nucleocytosolic acetyl‐CoA‐synthetase (Acs2p), responsible for conversion of acetate to acetyl‐CoA.…”
Section: Resultsmentioning
confidence: 96%
“…In other cases the inhibition by copper takes place only in the presence of reductants like ascorbate. Some examples are acetylcholinesterase [23], phosphoglucomutase [29], acetyl-CoA hydrolase [30] and catalase [31]. The deleterious effect of the axorbate/ Cu(11) mixture is usually observed only in the presence of oxygen since the mechanism of inactivation involves oxygen radicals generated in a Fenton-type reaction [32].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its extreme cold lability, this enzyme had to be purified at room temperature [1–5,9–15], which caused a great loss of the enzyme activity, presumably due to denaturation of the enzyme protein by oxidation and degradation by contaminating proteases. Recently, we found that Triton X‐100, a stabilizer for the membranous proteins and a cytosolic phospholipase A 2 [16], stabilizes CACH also (unpublished data).…”
mentioning
confidence: 99%